Needle biopsy through the abdominal wall for the diagnosis of gastrointestinal stromal tumour – Does it increase the risk for tumour cell seeding and recurrence?. (May 2016) - Eriksson, Mikael; Reichardt, Peter; Sundby Hall, Kirsten; Schütte, Jochen; Cameron, Silke; Hohenberger, Peter; Bauer, Sebastian; Leinonen, Mika; Reichardt, Annette; Rejmyr Davis, Maria; Alvegård, Thor; Joensuu, Heikki
Abstract: Purpose: Preoperative percutaneous transabdominal wall biopsy may be considered to diagnose gastrointestinal stromal tumour (GIST) and plan preoperative treatment with tyrosine kinase inhibitors when an endoscopic biopsy is not possible. Hypothetically, a transabdominal wall biopsy might lead to cell seeding and conversion of a local GIST to a disseminated one. We investigated the influence of preoperative needle biopsy on survival outcomes. Methods: We collected the clinical data from hospital case records of the 397 patients who participated in the Scandinavian Sarcoma Group (SSG) XVIII/Arbeitsgemeinschaft Internistische Onkologie (AIO) randomised trial and who had a transabdominal fine needle and/or core needle biopsy carried out prior to study entry. The SSG XVIII/AIO trial compared 1 and 3 years of adjuvant imatinib in a patient population with a high risk of GIST recurrence after macroscopically radical surgery. The primary end-point was recurrence-free survival (RFS), and the secondary end-points included overall survival (OS). Results: A total of 47 (12.0%) out of the 393 patients with data available underwent a percutaneous biopsy. No significant difference in RFS or OS was found between the patients who underwent or did not undergo a percutaneous biopsy either in the entire series or in subpopulation analyses, except for a statistically significant RFS advantage for patients who had a percutaneous biopsy and a tumour ≥10 cm in diameter. Conclusion: A preoperative diagnostic percutaneous biopsy of a suspected GIST may not increase the risk for GIST recurrence in a patient population who receive adjuvant imatinib after the biopsy. Highlights: A percutaneous biopsy to diagnose gastrointestinal stromal tumour (GIST) could lead to seeding of GIST cells. It is not known whether such a biopsy increases the risk for recurrence. An analysis based on the adjuvant trial Scandinavian Sarcoma Group XVIII/Arbeitsgemeinschaft Internistische Onkologie was performed. In this analysis a preoperative biopsy did not impact survival end-points.